Potential effects of UV radiation on photosynthetic structures of the bloom-forming cyanobacterium Cylindrospermopsis raciborskii CYRF-01 - Noyma, Natália P.; Silva, Thiago P.; Chiarini-Garcia, Hélio; Amado, André M.; Roland, Fábio; Melo, Rossana C. N. (Frontiers in Microbiology, 2015)
Cyanobacteria are aquatic photosynthetic microorganisms. While of enormous ecological importance, they have also been linked to human and animal illnesses around the world as a consequence of toxin production by some species. Cylindrospermopsis raciborskii, a filamentous nitrogen-fixing cyanobacterium, has attracted considerable attention due to its potential toxicity and ecophysiological adaptability. We investigated whether C. raciborskii could be affected by ultraviolet (UV) radiation. Non-axenic cultures of C. raciborskii were exposed to three UV treatments (UVA, UVB or UVA + UVB) over a 6 h period, during which cell concentration, viability and ultrastructure were analyzed. UVA and UVA + UVB treatments showed significant negative effects on cell concentration (decreases of 56.4% and 64.3%, respectively). This decrease was directly associated with cell death as revealed by a cell viability fluorescent probe. Over 90% of UVA + UVB- and UVA-treated cells died. UVB did not alter cell concentration, but reduced cell viability in almost 50% of organisms. Transmission electron microscopy (TEM) revealed a drastic loss of thylakoids, membranes in which cyanobacteria photosystems are localized, after all treatments. Moreover, other photosynthetic- and metabolic-related structures, such as accessory pigments and polyphosphate granules, were damaged. Quantitative TEM analyses revealed a 95.8 % reduction in cell area occupied by thylakoids after UVA treatment, and reduction of 77.6 % and 81.3 % after UVB and UVA + UVB treatments, respectively. Results demonstrated clear alterations in viability and photosynthetic structures of C. raciborskii induced by various UV radiation fractions. This study facilitates our understanding of the subcellular organization of this cyanobacterium species, identifies specific intracellular targets of UVA and UVB radiation and reinforces the importance of UV radiation as an environmental stressor.